Dihydropyracyloporphyrins. Issue 52 (24th December 2020) - Rauen, Patrick J.; Lash, Timothy D.
Graphical abstract: Abstract: A pyrrole ethyl ester with a fused dihydropyracylene unit was prepared by reacting 5-nitro-1, 2-dihydropyracylene with ethyl isocyanoacetate in the presence of a phosphazene base. Cleavage of the ester moiety, followed by reaction with an acetoxymethylpyrrole and acetic acid in refluxing ethanol, afforded a tripyrrane, and subsequent '3 + 1' condensation with a pyrrole dialdehyde gave a dihydropyracyloporphyrin. Cyclotetramerization of the dihydropyracylopyrrole with benzaldehyde and BF3 ·Et2 O gave a sterically crowded tetrakis(dihydropyracylo)-porphyrin and the reduced five-membered rings proved to be an excellent NMR probe for conformational mobility. The new porphyrins and their nickel(II) complexes also showed potentially valuable highly red shifted UV–vis spectra.